Inter‐ and intra‐fractional stability of rectal gas in pelvic cancer patients during MRIgRT. Issue 1 (30th November 2020) - Shortall, J.; Vasquez Osorio, E.; Cree, A.; Song, Y.; Dubec, M.; Chuter, R.; Price, G.; McWilliam, A.; Kirkby, K.; Mackay, R.; van Herk, M.
Abstract : Purpose: Due to the electron return effect (ERE) during magnetic resonance imaging guided radiotherapy (MRIgRT), rectal gas during pelvic treatments can result in hot spots of over‐dosage in the rectal wall. Determining the clinical impact of this effect on rectal toxicity requires estimation of the amount and mobility (and stability) of rectal gas during treatment. We therefore investigated the amount of rectal gas and local inter‐ and intra‐fractional changes of rectal gas in pelvic cancer patients. Methods: To estimate the volume of gas present at treatment planning, the rectal gas contents in the planning computed tomography (CT) scans of 124 bladder, 70 cervical and 2180 prostate cancer patients were calculated. To estimate inter‐ and intra‐fractional variations in rectal gas, 174 and 131 T2‐w MRIs for six cervical and eleven bladder cancer patients were used. These scans were acquired during four scan‐sessions ( 20–25 min each) at various time‐points. Additionally, 258 T2‐w MRIs of the first five prostate cancer patients treated using MRIgRT at our center, acquired during each fraction, were analyzed. Rectums were delineated on all scans. The area of gas within the rectum delineations was identified on each MRI slice using thresholding techniques. The area of gas on each slice of the rectum was used to calculate the inter‐ and intra‐fractional group mean, systematic and random variations along the length of the rectum. The cumulative dose perturbation as a result of the gas was estimated. Two approaches were explored: accounting or not accounting for the gas at the start of the scan‐session. Results: Intra‐fractional variations in rectal gas are small compared to the absolute volume of rectal gas detected for all patient groups. That is, rectal gas is likely to remain stable for periods of 20–25 min. Larger volumes of gas and larger variations in gas volume were observed in bladder cancer patients compared with cervical and prostate cancer patients. For all patients, local cumulative dose perturbations per beam over an entire treatment in the order of 60 % were estimated when gas had not been accounted for in the daily adaption. The calculated dose perturbation over the whole treatment was dramatically reduced in all patients when accounting for the gas in the daily set‐up image. Conclusion: Rectal gas in pelvic cancer patients is likely to remain stable over the course of an MRIgRT fraction, and also likely to reappear in the same location in multiple fractions, and can therefore result in clinically relevant over‐dosage in the rectal wall. The over‐dosage is reduced when accounting for gas in the daily adaption.